Nitric oxide generation by microwave capillary discharges under thermal control at atmospheric pressure - Sterie, V. A.; Zhao, Y.; Stancu, G. D. (Frontiers in Physics, 2023)
Nitric oxide (NO) was generated inside capillary microwave discharges of 1-mm diameter, operating at 2.4 ÷ 2.5 GHz in mixtures of argon and air at atmospheric pressure. Time-resolved Mid-IR Quantum Cascade Laser Absorption Spectroscopy (QCLAS) was employed to measure the absolute density of NO molecules in ex situ conditions. The capillary post-discharge was coupled into a 50-cm White multi-pass cell where the laser was scanned over the ro-vibrational transition R (6.5), v(0→1), in the NO electronic ground state X1/2 at 1900.076 cm−1. It was found that NO density can be tuned over three orders of magnitude by varying the gas mixture and the discharge power. Enhancing the heat flux through the capillary has significantly extended the operating range of the discharge, increased the NO density and flowrate by almost one order of magnitude, and consequently reduced the energy cost. Molar fractions of NO up to 3,000 ppm (7.1 × 1016 cm−3) with flowrates up to 7.2 sccm for discharge powers below 100 W have been obtained. Using a thermally controlled configuration, the energy cost of NO was found to be comparable to other efficient plasma sources at atmospheric pressure.